The independent directors of Malaysian listed firms and their busyness - Abdullah, Shamsul Nahar (2013)
The objective of this paper is to examine the extent to which the independent directors are independent of management and to what extent they are busy. From a sample of 200 non-finance Malaysian listed firms for the 2009 and 2010 financial years, it is observed that the almost 60% of the independent directors have professional backgrounds and another 20% are either serving or retired government servants. Hence, by virtue of their training, a majority of them are independent and objective. Findings also show that the largest shareholders of the sample firms are as follow: families (66%), government (4%); institutions (8%). On average, there are 1.5 family members or 21% of the board size. While the role of senior independent directors is very important in a concentrated ownership environment, only one quarter of the sample firms appoint senior independent directors. Out of 135 family owned firms, only one fifth appoint senior independent directors. As for board chairman, only 30% of sample firms and family owned firms appoint independent directors as the board chairman. In terms of independent directors’ busyness, on average, each independent director holds one directorship in other listed firms. All independent directors seem to attend all board meetings. Hence, the independent directors appear to be not so busy and are able to discharge their duties.